2005
DOI: 10.4315/0362-028x-68.10.2112
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Virus Attachment Patterns to Butterhead Lettuce

Abstract: Enteric viruses account for most foodborne illness in the United States. The objective of this study was to determine whether the isoelectric point (pI) of viruses such as feline calicivirus (FCV), echovirus 11, and bacteriophages phiX174 and MS2 had any effect on their attachment to butterhead lettuce. The adsorption of virus particles to the lettuce was variable. Bacteriophage MS2 was the only virus that fit the current Derjaguin-Landau-Verway-Overbeek model of virus attachment. Echovirus 11 had the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 22 publications
4
37
0
2
Order By: Relevance
“…Additionally, the influence of individual food matrices and viral strains on the overall efficiency is also likely to be significant. The differences in the viral strains may be correlated with different stabilities under drying conditions and different levels of attachment to the food surface and the viral resistance at low pH (1,31,51). Recently, Vega et al (51) demonstrated that viruses exhibited different attachment patterns depending on their isoelectric point, suggesting that the use of a particular pH buffer to release viruses from food surfaces could selectively recover a particular type or group of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the influence of individual food matrices and viral strains on the overall efficiency is also likely to be significant. The differences in the viral strains may be correlated with different stabilities under drying conditions and different levels of attachment to the food surface and the viral resistance at low pH (1,31,51). Recently, Vega et al (51) demonstrated that viruses exhibited different attachment patterns depending on their isoelectric point, suggesting that the use of a particular pH buffer to release viruses from food surfaces could selectively recover a particular type or group of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The major driving force behind virus attachment should be physicochemical forces that control the interactions between viruses and plant surfaces. But little is known about such interactions, and different viruses and phages have exhibited viable attachment patterns (21). Since enteric viruses are frequently associated with feces and biosolids in the environment, information on interactions between solids, viruses, and leaf surfaces can contribute to reliable methods that prevent attachment or remove attached viral particles.…”
Section: Vol 76 2010 Attachment and Internalization Of Virus On Letmentioning
confidence: 99%
“…Virus adsorption to lettuce has also been found to vary depending on the strain and surface properties of the virus. Feline calicivirus (FCV) had a higher level of attachment to lettuce when the pH was above its isoelectric point (pI), while for bacteriophage MS2, strong adsorption to lettuce was observed at a value below its pI (21). As viruses are small particles that most likely are associated with feces when they are present in biosolids or animal manure, it is important to understand the mechanism of their attachment to and internalization by leafy greens if biosolids or manure is used in vegetable production.…”
mentioning
confidence: 99%
“…식품에 존재하는 바이러 스의 검출한계는 분석방법 (예로 RT-PCR, RT-PCR후 nested PCR 또는 real-time PCR), 식품의 매트릭스 차이, 시료의 양, 분석하고자하는 바이러스의 strain, 사용된 primer 등 에 의해 달라질 수 있으므로 검출방법 간의 직접비교는 힘들다 19,31) . 하지만 본 연구를 통해 개발된 검출방법의 검 출한계(10-25 g 식품당 3.125-12.5 RT-PCR unit)는 보고된 검출한계(6-50 g 식품당 10-1500 RT-PCR units) 13,14,22,29,32,38) 와 비슷하거나 더 나았다. RT-PCR unit당의 노로바이러스 게놈 copy의 수는 약 10-42로 보고된 바 있다.…”
Section: Resultsunclassified
“…발효식품이나 가공식품의 경우 상대적으로 안전할 것으로 판단되었으나 최근 몇 차례 학 교급식 식중독 사고의 원인식품이 김치로 밝혀짐에 따라 해산물과 야채/과일 외에도 가열처리가 동반되지 않는 다 *Correspondence to: Weon Sang Choi, Department of Biotechnology, Dongguk University-Gyeongju, Gyeongju 780-714, Korea Tel: 82-54-770-2227, Fax: 82-54-770-2386 E-mail: weonsang@dongguk.ac.kr 양한 식품들이 모두 원인이 될 수 있을 것으로 보인다. 현재까지 굴 등의 해산물 [7][8][9][10] , 채소류 [11][12][13][14][15][16][17][18] , 과일류 15,19,20,21) 외 다양한 식품 15,16,[22][23][24] 에서 오염된 바이러스를 검출하는 방법이 개발된 바 있으나 식품마다 매트릭스(matrix) , Beef extract 21,26) , 아미노산 buffer 12,19,27) , Tris buffer 28) , 아미노산-NaCl buffer 12,15,17,18,29) , Tris-glycine buffer 12,13) 또는 이들 buffer의 combination .…”
unclassified